Sea Country Issue 2 1995 - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 1995)
The second issue of Sea Country is written by staff from the Great Barrier Reef Marine Park Authority (GBRMPA) and the Queensland Department .of Environment and Heritage (QDEH), and Community Rangers from Cape York. This newsletter will keep you up to date with sea country issues & Cape York.
Keywords: Marine parks; Aboriginal communities; People and the Reef; Traditional owners; Reef-wide